Analysis Of Canvas Business Models In Vaboja (Vas Bonggol Jagung) Using Corn Waste - Sartika Sari; Rondi Saputra; Syuhada Wulantiya (JASc (Journal of Agribusiness Sciences), 2019)
The Business Model is a method that helps companies to tell about the company's internal conditions. Through the bussines model canvas, the company can display in a simple yet comprehensive manner the nine essential components of the business such as customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships and cost structures. So that this method can be used to analyze a company's business model such as VABOJA (Corncob Vase). This study aims to analyze the business model of VABOJA (Corncob Vase) using Bussines Model Canvas. Vaboja analysis is a vase of corn stumps that reuse waste corn into more valuable (valuable) goods or products. This product is simple but the use of the waste makes this product has an economic value. In addition to reducing the waste that is around the community, this product can also be a promising business because the raw materials in making these products are very large and very easy to obtain. a high level of creativity is needed so that the products produced can make consumers satisfied and come back to order this product. With this analysis, a company can manage the business that will be run so that it can get profits and get a good response from the community for the products produced. Data is obtained from the results of surveys by consumers (housewives) in the city of Medan and surrounding areas to find out the advantages and disadvantages of the product and what forms and designs the customers want so that this business can continue and become a profitable business even become a business that can penetrate into the international market.